Regulation of risk : transport, trade and environment in perspective - Basu Bal, Abhinayan; Rajput, Trisha; Argüello Moncayo, Gabriela, 1983-; Langlet, David; Malmberg, Lars-Göran, 1953- (International Law E-Books Online, Collection 2023., 2023)
"This book provides a comprehensive insight into regulation of risk in transport, trade and environment. Contributions provide national, regional and international perspectives on pressing questions: How is risk conceived in light of novel technological deployment, climate change, political upheaval, evolving geopolitics, and the COVID-19 pandemic? What legal tools such as contractual frameworks and governance structures are available to manage the changing landscape of risk? This book highlights the importance of dialogue and collaborative decision-making on risk between policymakers, institutions, societal stakeholders and the scientific community"--